Mapping Molecular Orientation with Phase Sensitive Vibrationally Resonant Sum-Frequency Generation Microscopy - Han, Yang (2013)
We demonstrate a phase sensitive, vibrationally resonant sum-frequency generation (PSVR-SFG) microscope that combines high resolution, fast image acquisition speed, chemical selectivity, and phase sensitivity. Using the PSVR-SFG microscope, we generate amplitude and phase images of the second-order susceptibility of collagen I fibers in rat tail tendon tissue on resonance with the methylene vibrations of the protein. We find that the phase of the second-order susceptibility shows dependence on the effective polarity of the fibril bundles, revealing fibrous collagen domains of opposite orientations within the tissue. The presence of collagen microdomains in tendon tissue may have implications for the interpretation of the mechanical properties of the tissue. [Image: see text]